A Uniquely Shaped Rod Improves Curve Correction in Surgical Treatment of Adolescent Idiopathic Scoliosis. Issue 14 (15th July 2016) - Gehrchen, Martin; Ohrt-Nissen, S⊘ren; Hallager, Dennis W.; Dahl, Benny
Abstract : Study Design: A retrospective cohort study. Objective: The aim of this study is to determine the initial curve correction in patients surgically treated for adolescent idiopathic scoliosis (AIS) using either beam-like rods (BRs) or traditional circular rods (CRs). Summary of Background Data: Posterior fusion using all pedicle screw instrumentation has become the standard for the surgical treatment of AIS. Traditionally, the rod is circular in the cross-sectional plane. Recent biomechanical studies suggest that a beam-like structure of the rod may enhance the stiffness of the construct and thereby possibly improve curve correction. Methods: Two consecutive series of patients surgically treated for AIS between May 2011 and May 2015 were included in the study. Patients were all treated with an ultralow profile all-pedicle screw implant system. In the first series, conventional 5.5 mm CoCr CR were used, and in the second series, 5.5 mm CoCr BR were used. Antero-posterior and lateral radiographs preoperatively and within seven days after surgery were used to measure the correction obtained. Results: The first 60 patients were operated with CR and the subsequent 69 with BR. There was no statistical difference in age, gender, preoperative curve magnitude, Lenke type, or number of levels instrumented ( P  = 0.451). Major curve correction was significantly better in the BR group than in the CR group (66 vs. 57%) ( P  < 0.001). We found no difference in preoperative flexibility, secondary curve correction, sagittal balance, or coronal balance ( P  > 0.058). A postoperative decrease in thoracic kyphosis was seen with no significant difference between groups. Median T5-T12 change was −7° versus −3° for BR and CR, respectively ( P  = 0.051). Conclusion: A BR design results in a significantly better curve correction than conventional rods, but the difference is moderate and the clinical value is uncertain. Level of Evidence: 3